Meningkatkan Aktivitas Belajar Fisika Siswa dengan Model STAD (Student Team Achievement Division) Disertai LKS di Kelas X.4 SMA Negeri Balung pada Materi Listrik Dinamis - Aris Singgih Budiarso (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2014)
This aim of study to describe model Student TeamAchievement Division with worksheet to improve studentlearning activities on X.4 physics class Balung Senior HighSchool. The population of study is comprising X.4 classconsist of 38 student, the purposive sampling usesampling area method. The technique of data analysis beused average score to determine the level of studentactivity. Based on the calculations, the physics studentsthat the learn activities use model Student TeamAchievement Division with worksheet on the matterdynamic power can increase middle became high active.